ПЗС-датчики для контроля параметров геометрических размеров волокна - Селенкова, Н. П.; Баранник, М. Н. (ХНУРЭ, 2012)
The devices with the charging communication used for control of parameters of the fibre geometrical sizes are considered in article. Equipment for change of a focal plane of control system is shown.
Keywords: optoelectronic gages; device with charging communication